A Review -Automobile Design and Implementation of CAN bus Protocol - V. Deepan; R. Balamurugan; K. Sakthivel; K.Kanthavel; Palani (Journal of Power Electronics and Devices, 2022)
The most extensively studied communication protocol for the automotive industry is called Controller Area Network (CAN). We are now moving towards the world of autonomous artificial intelligence (AI) based or semiautonomous vehicle systems, which are capable of providing the best in class driverless experience globally. We require a very quick communication protocol in addition to an efficient implementation of vehicle and computer convergence. We can build and deploy a system with a single onboard computer that remotely controls vehicle characteristics thanks to CAN. Researchers are anticipating the Wireless Controller Area Network (WCAN), which has the potential to eventually expand into the IoT space and flourish in the development of an efficient transportation system. The Controller Area Network (CAN) is a good option for the automotive industry because of its ease of use, low cost, and connectivity with multiple nodes using a single wiring pair. The purpose of this paper is to develop a hardware proposal for CAN bus communication between nodes. To monitor and control the various parameter values, transfer data on the CAN bus, and send control signals to another node, a Node-to-Node communication link has been established. With the aid of LABVIEW HIL, which is capable of monitoring and controlling various CAN signals, this Hardware is connected in a loop.